Flipped versions of the universal 3-3-1 and the left-right symmetric models in [SU(3)]3: a comprehensive approach (2017)
ABSTRACT: By considering the 3-3-1 and the left-right symmetric models as low energy effective theories of the SU(3)C SU(3)L SU(3)R (for short [SU(3)]3) gauge group, alternative versions of these models are found. The new neutral gauge bosons of the universal 3-3-1 model and its ipped versions are presented; also, the left-right symmetric model and its ipped variants are studied. Our analysis shows that there are two ipped versions of the universal 3-3-1 model, with the particularity that both of them have the same weak charges. For the left-right symmetric model we also found two ipped versions; one of them new in the literature which, unlike those of the 3-3-1, requires a dedicated study of its electroweak properties. For all the models analyzed, the couplings of the Z0 bosons to the standard model fermions are reported. The explicit form of the null space of the vector boson mass matrix for an arbitrary Higgs tensor and gauge group is also presented. In the general framework of the [SU(3)]3 gauge group, and by using the LHC experimental results and EW precision data, limits on the Z0 mass and the mixing angle between Z and the new gauge bosons Z0 are obtained. The general results call for very small mixing angles in the range 10-3 radians and MZ0 > 2.5 TeV.